COLLABORATIVE GOVERNANCE IN THE DEVELOPMENT OF GUNUNG MASIGIT TOURISM VILLAGE, CIPATAT SUB-DISTRICT, WEST BANDUNG DISTRICT: AN IMPACT ANALYSIS OF VILLAGE DIGITIZATION - Bayu Septiansyah; Toto Kushartono (Universitas Jenderal Ahmad Yani, 2025)
This research aims to analyse the application of Collaborative Governance in the development of Gunung Masigit Tourism Village in Cipatat Sub-district, West Bandung Regency, with a focus on the impact of village digitalisation. Through a qualitative approach, this research explores how interactions between stakeholders, including the village government, community, and private sector, influence tourism development in the village. The analytical model used refers to Ansell and Gash's concept with key indicators such as Face-to-Face Dialogue, Building Trust, Commitment to Process, Sharing Understanding, and Small Wins. The results show that effective face-to-face dialogue allows all parties to build trust and understanding, which is very important in the context of collaboration. The successful development of Gunung Masigit Tourism Village is not only determined by the presence of digital infrastructure, but also by the active commitment of the local community and support from the private sector. Small wins in this process, such as the launch of local tourism programmes and the use of technology for promotion, contributed to increased community participation and tourist visits. From these findings, it is recommended that the village government continue to strengthen cooperation between stakeholders, as well as utilise digitalisation as a tool to increase the attractiveness and sustainability of tourism in Gunung Masigit Tourism Village. This research is expected to provide insights for better policy development in sustainable tourism village management.